Diseño de un Controlador por Torque Calculado CTC de un Robot Manipulador Tipo SCARA (2011)
A control by reference model Computed Torque Control (CTC) was implemented through simulation on a SCARAtype robot manipulator with four degrees of freedom, in order to carry out the study of the benefits of the algorithm to a set of tests. The CTC is a classical law in control of industrial manipulators and it uses the feedback of a signal that cancels the effects of gravity, friction, inertia tensor of the manipulator, coriolis and centrifugal forces. The controllers were evaluated by calculating the tracking error, rejection of disturbance and errors in the model.